2017
DOI: 10.21276/ijlssr.2017.3.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Traditional Knowledge of Medicinal Flora and its Contribution to Livelihood Enhancement in the Doon-Valley, Uttrakhand (India)

Abstract: ABSTRACT-Uttrakhand has tremendous potential for medicinal plants cultivation and in becoming one of the important options for sustainable livelihood in the Doon valley as well as all hilly regions. Doon-valley, Uttrakhand can take advantages of increasing demand and low availability of medicinal and aromatic plants resources in the other parts of the country and start to grow highly valuable medicinal plants in high altitude areas. Medicinal and aromatic plants can play an important role in the subsistence li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…It was even more surprising that only 2.6% of the local community members managed to identify all the medicinal plants, while up to 13% of the local community members could only identify less than 20% of the plant species. ese results suggest an erosion of traditional medicinal knowledge, which concurs with other studies elsewhere [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…It was even more surprising that only 2.6% of the local community members managed to identify all the medicinal plants, while up to 13% of the local community members could only identify less than 20% of the plant species. ese results suggest an erosion of traditional medicinal knowledge, which concurs with other studies elsewhere [54,55].…”
Section: Discussionsupporting
confidence: 92%
“…Based on FIVs, the important families included Mimosaceae, Polygonaceae, Papilionaceae, Moraceae, Lamiaceae, Asteraceae, Rhamnaceae, Sapindaceae, Myrtaceae and Asclepiadaceae. Mimosaceae is virtually always the most diverse family throughout the subcontinent (Sher et al 2011 ; Wariss et al 2014 ). Papilionaceae has a dominant position in plant families (Zeb et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemicals or plant extract could be used to treat different diseases and new formulation for the drug discovery in pharmaceuticals . Medicinal plants play an important role in the continuation of livelihood improvement, especially women in an environmentally sustainable manner while maintaining the biodiversity of these natural products (Sharma et al, 2017). World Health Organization has reported that about 80% of the world's population depends on traditional medicine for their preliminary healthcare needs.…”
Section: International Journal Of Zoological Investigations Issn: 2454-3055mentioning
confidence: 99%